IMPLEMENTASI PROGRAM PENDIDIKAN LINGKUNGAN HIDUP PADA SISWA SEKOLAH DASAR UNTUK MENANAMKAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN - Febriyanto, Eko Yudi (Politeknik Perkeretaapian Indonesia Madiun, 2025)
This study aims to describe the implementation of environmental education programs in fostering environmental care character in Kebonan 2 State Elementary School students, Lumajang Regency. The research method uses a qualitative approach with data collection techniques through participatory observation and documentation during the implementation of the program. The results of the study show five main programs implemented: (1) Clean Friday to familiarize the cleanliness of the school environment; (2) Canva Digital Poster Training to increase students' creativity in conveying environmental messages; (3) Natural Disaster Mitigation Mini Seminar to strengthen students' understanding of disaster risk reduction; (4) Making Waste Recycling Crafts as an effort to manage waste based on creativity; and (5) Environmental Poster Competition as a medium for environmental awareness campaigns. The implementation of this program has successfully increased student participation in cleaning activities, graphic design skills, and an understanding of recycling and disaster mitigation. However, students' enthusiasm still needs to be increased through more interactive approaches such as using environment-themed games. The conclusion of the study underlines that the integration of environmental programs based on direct practices is effective in forming the character of caring for the environment. It is recommended that schools strengthen collaboration with local communities such as the Lumajang Children's Creative House and use digital technology such as publication of the results of activities on school social media to expand the impact of the program.